The effects of jumping distance on the landing mechanics after a volleyball spike - Marquez, W. Q.; Masumura, M.; Ae, M. (Sports Biomechanics, 2009)
The purpose of this study was to assess the effects of jumping distance on the landing mechanics after a volleyball spike, to help in injury prevention and training for safer landing. Ground reaction forces and three-dimensional kinematic data were collected from six male university right-handed volleyball players under "Normal" and "Long" jumping distance conditions of landing after a spike. The results revealed that the landings under the Long jumping distance condition produced significantly greater centre of gravity velocities and larger mean loading rates. Although data were collected for bilateral landings with the two feet contacting the force platform at the same time, landing motion was asymmetric and the left leg was considered to play a more critical role in the absorption of the landing impact. The trunk and hip positions at the initial contact with the floor and the range of motions of the knee and ankle were key kinematic parameters for reducing the vertical peak ground reaction forces and extending the time from the initial contact to the occurrence of this peak force, which consequently reduced the mean loading rate upon landing.